Validation of the German version of the Perceived Cohesion Scale - Marietta Lieb; Werner Adler; Regina Herold; Yesim Erim; Eva Morawa (International Journal of Occupational Medicine and Environmental Health)
Objectives Team or group cohesion is a multifaceted construct with a variety of definitions and measurement instruments. However, most of these measures are context and group-specific and/or time-consuming. There is no adaptable and economic measure of group cohesion in Germany. Therefore, the aim of this study was to validate the German version of the 6-item Perceived Cohesion Scale (PCS) in a sample of adult nurses in a German University Hospital.